Strangers [large type] - Pronzini, Bill (Pronzini, Bill. "Nameless Detective" mysteries., 2014)
Cody Hatcher is the kind of teenager you don't want your kids hanging with. That's why the citizens of Mineral Springs have no problem believing that he's guilty of three rapes. His mother, Cheryl, an old lover of the Nameless Detective, is being harassed by vindictive townspeople. With few to help him and plenty to get in his way, Nameless must work to prove Cody innocent. It's a classic situation for an iconic private investigator.--